A Climate Coffee Chat, Post-Food Systems Summit Dialogue North America - Baethgen, Walter; Boettiger, Sara; Turner, Jacquelyn (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS), life science company Bayer and Columbia University's Earth Institute organized an online Food Systems Summit Dialogue (FSSD) event with stakeholders based in North America.